Intra- and inter-plant variability of quinolizidine alkaloids in narrow-leaf lupin seeds, grown under different day/night cycles - Tawfeek Khedr; Ling-Ling Gao; Lars G. Kamphuis; Angéla Juhász; Michelle L. Colgrave (Heliyon)
Inconsistent fluctuation of quinolizidine alkaloid (QA) content in lupin seeds is often observed, sometimes surpassing safe thresholds (>200 mg/kg) yet lacks a clear explanation. This study aimed to investigate the intra-plant variability of QA content in three narrow-leaf lupin genotypes: Tanjil, Quillinock, and P22660 using LC-MS/MS. QA levels in seeds from the same pods showed <30 % variation, while those from different pods in the same plant sometimes surpassed inter-plant variations (up to 94 %). The average measured QA concentrations under speed breeding conditions in Quillinock, Tanjil, and P22660 were 36, 103, and 27,000 mg/kg, respectively. The impact of longer daylight hours (16h day/8h night), a practice used in speed breeding, on QA content in the cultivar Tanjil was also studied. Longer daylight hours yielded elevated QA levels in Tanjil seeds (103 mg/kg) compared to those grown in a greenhouse (10–13h daylight, 32 mg/kg).